A survey of medicinal plants used by the inhabitants in Padiyur, Kangeyam Taluk, Tirupur District, Tamil Nadu, India - Devasenathipathi, M.; Rajeswari, S.; Anuja, J.; Athira, S. (Current Botany, 2025)
In this investigation, the local people were enquired to know about the common medicinal plants and their usage in their day-to-day life. An attempt was made to make a systematic approach to record the local name, binomial name, and mode of administration from the inhabitants of Padiyur, Kangeyam Taluk, Tirupur District. The ethnomedicinal data were collected and documented by randomly planned visits from December 2020 to May 2021. This paper provides the herbal preparations of the medicinal plants which are used till now. A total of 105 species belonging to 47 families were documented. The ethnobotanical work with valid information was analyzed and verified using the Informant Consensus Factor (ICF), Use Value Index (UVI) and Relative Frequency of Citation (RFC).